Development of a multiplex qRT-PCR assay for detection of classical swine fever virus, African swine fever virus, and Erysipelothrix rhusiopathiae - Zhao, Liang; Wen, Xiao-Hui; Jia, Chun-Ling; Zhou, Xiu-Rong; Luo, Sheng-Jun; Lv, Dian-Hong; Zhai, Qi (Frontiers in Veterinary Science, 2023)
Classical swine fever virus (CSFV), African swine fever virus (ASFV), and Erysipelothrix rhusiopathiae (E. rhusiopathiae) remain endemic in many parts of China. Co-infections make distinguishing their clinical symptoms and pathological changes difficult. This study developed a multiplex real-time quantitative reverse transcription polymerase chain reaction (multiplex qRT-PCR) that can simultaneously detect CSFV, ASFV, and E. rhusiopathiae. Three sets of primers and probes were designed to target the CSFV 5΄ untranslated region, ASFV p72 gene, and E. rhusiopathiae 16sRNA gene. Multiplex qRT-PCR for simultaneous differential detection of these three pathogens was developed after optimizing reaction parameters such as annealing temperature, primer and probe concentrations, amplification cycles, etc. The multiplex qRT–PCR could detect CSFV, ASFV, and E. rhusiopathiae simultaneously but could not amplify other porcine pathogens. The assay’s limit of detection (LOD) was 2.89 × 102 copies/μl for CSFV, ASFV, and E. rhusiopathiae. All correlation coefficients (R2) at higher than 0.99, and the amplification efficiency was 98%, 90%, and 84%, respectively. All correlation coefficients (R2) were higher than 0.99, and the efficacy of amplification was 84%. In a repeatability test utilizing standard recombinant plasmids, the intra- and inter-assay coefficients of variation (CVs) were less than 2.27 and 3.79 percent, respectively. Lastly, 150 clinical samples were used to evaluate the assay’s applicability in the field. The positive rates of CSFV, ASFV, and E. rhusiopathiae were 1.33%, 0, and 3.33%, respectively. And no co-infection among the three pathogens was found. The concordance rate between the multiplex qRT-PCR and single-plex commercial PCR kits reached 100%. This study's multiplex qRT-PCR could provide a rapid, sensitive, and specific method for the simultaneous and differential detection of CSFV, ASFV, and E. rhusiopathiae.